Respuesta :

Answer:

First Box: Factor by difference of squares

Second Box: It has all perfect squares

Third Box: see my work

Step-by-step explanation:

We have the equation [tex]4x^2=36[/tex]

Before we do anything, let us bring all of the terms to the left side

[tex]4x^2-36=0[/tex]

Now that we have moved the terms to one side, it is clear that we have a difference of squares.

-Work-

[tex]4x^2=36\\\\4x^2-36=0\\\\(2x+6)(2x-6)=0\\\\[/tex]

-

[tex]2x+6=0\\\\2x=-6\\\\x=-3[/tex]

-

[tex]2x-6=0\\\\2x=6\\\\x=3[/tex]